Comparative efficacy of non-electric cooling techniques to reduce nutrient solution temperature for the sustainable cultivation of summer vegetables in open-air hydroponics - Nisar, Muhammad Mohsin; Mahmood, Rashid; Tayyab, Salman; Anees, Moazzam; Nadeem, Faisal; Bibi, Sadia; Waseem, Faiza; Ahmed, Nazir; Li, Jing; Song, Zhao (Frontiers in Plant Science, 2024)
The cultivation of summer vegetables in open-air nutrient film technique (NFT) hydroponics is limited due to the elevated nutrient solution temperature (NST). In this regard, non-electric evaporative-cooling techniques were explored to maintain NST in open-air NFT hydroponics. Four cooling setups were employed by wrapping polyvinyl chloride (PVC) grow pipes with one and two layers of either wet or dry jute fabrics and attaching them with coiled aluminum pipe buried inside a) wet sand-filled brick tunnels (Cooling Setup I), b) two inverted and vertically stacked earthen pots (Cooling Setup II), c) two inverted and vertically stacked earthen pots externally wrapped with wet jute fabric (Wrapped Cooling Setup II), and d) an earthen pitcher wrapped with wet jute fabric (Cooling Setup III). Wrapping grow pipes with two layers of wet jute fabric reduced NST by 5°C as compared to exposed (naked) grow pipes. The double-layer jute fabric-wrapped grow pipes produced 182% more reduction in NST in comparison to single layer-wrapped grow pipes. Additionally, the installation of Wrapped Cooling Setup II and Cooling Setup III outperformed Cooling Setup I and Cooling Setup II through NST reduction of approximately 4°C in comparison to control. Interestingly, Cooling Setup III showed its effectiveness through NST reductions of 193%, 88%, and 23% during 11 a.m.–12 p.m. as compared to Cooling Setup I, Cooling Setup II, and Wrapped Cooling Setup II, respectively. In contrast, Wrapped Cooling Setup II caused NST reductions of 168%, 191%, and 18% during 2–3 p.m. in comparison to Cooling Setup I, Cooling Setup II, and Cooling Setup III, respectively. Thus, the double-layer jute fabric-wrapped grow pipes linked with Wrapped Cooling Setup II can ensure summer vegetable cultivation in open-air NFT hydroponics as indicated by the survival of five out of 12 vegetable plants till harvest by maintaining NST between 26°C and 28°C.